Predominant Components of the Tutorial Action in University Students - Guerrero-Ramírez, Julia (2019)
The research related to the practice of tutorial action in university students, aimed to determine the predominant component of tutorial, recognizing that tutorial in the university is gaining value and significance for the benefit of the students, as a support area, orientation and coverage during the educational procedure in its different academic, professional and personal dimensions. The study corresponds to the quantitative approach, deductive hypothetical and substantive method, non-experimental, cross-sectional or transactional and explanatory design, with a population of 2629 students whose representative sample was 335 participants. The results of the same showed that 67% of the students considered that the tutorial action they received was adequate, while 33%, also states that the predominant dimension was the academic development. It is concluded that the tutorial action did have a significant and predominant presence since it was considered as adequate within the development of university life in undergraduate students; situation that confirmed and revalued the attention to different needs and interests by the students responding to an education of integral development.